Profiles of Biomarkers of Excess Alcohol Consumption in Patients Undergoing Total Hip Replacement: Correlation with Function - Paul J. Jenkins; Andrew D. Duckworth; Francis P. C. Robertson; Colin R. Howie; James S. Huntley (The Scientific World Journal)
Aims. Patients who misuse alcohol may be at increased risk of surgical complications and poorer function following hip replacement. Identification and intervention may lead to harm reduction and improve the outcomes of surgery. The aim of this study was to determine the prevalence of biomarker elevation in patients undergoing hip replacement and to investigate any correlation with functional scores and complications. Methods. We performed a retrospective study that examined the profile of biomarkers of alcohol misuse in 1049 patients undergoing hip replacement. Results. Gamma-glutamyltransferase was elevated in 150 (17.6%), and mean corpuscular volume was elevated in 23 (4%). At one year general physical health was poorer where there was elevation of γGT, and the mental health and hip function was poorer with elevation of MCV. There were no differences in complications. Discussion. Raised biomarkers can alert clinicians to potential problems. They also provide an opportunity to perform further investigation and offer intervention. Future research should focus on the use in orthopaedic practice of validated screening questionnaires and more sensitive biomarkers of alcohol misuse. Conclusion. This study demonstrates a potential substantial proportion of unrecognised alcohol misuse that is associated with poorer functional scores in patients after total hip replacement.